Restoring calcium crosstalk between ER and mitochondria promotes intestinal stem cell rejuvenation through autophagy in aged Drosophila - Yao Zhang; Peng Ma; Saifei Wang; Shuxin Chen; Hansong Deng (Nature Communications)
Abstract Breakdown of calcium network is closely associated with cellular aging. Previously, we found that cytosolic calcium (CytoCa2+) levels were elevated while mitochondrial calcium (MitoCa2+) levels were decreased and associated with metabolic shift in aged intestinal stem cells (ISCs) of Drosophila. How MitoCa2+ was decoupled from the intracellular calcium network and whether the reduction of MitoCa2+ drives ISC aging, however, remains unresolved. Here, we show that genetically restoring MitoCa2+ can reverse ISC functional decline and promote intestinal homeostasis by activating autophagy in aged flies. Further studies indicate that MitoCa2+ and Mitochondria–ER contacts (MERCs) form a positive feedback loop via IP3R to regulate autophagy independent of AMPK. Breakdown of this loop is responsible for MitoCa2+ reduction and ISC dysfunction in aged flies. Our results identify a regulatory module for autophagy initiation involving calcium crosstalk between the ER and mitochondria, providing a strategy to treat aging and age-related diseases.